Effect of dietary supplementation with antioxidants and flavouring prototypes based on acorn and olive on the volatile profile of pork - Lisha Wang; Eline Kowalski; Marijke Aluwé; Sam Millet; Els Vossen; Stefaan De Smet (Meat Science, 2026)

Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

ACMT Position Statement: Preventing Cannabis Exposures in Children (2026) - Robert G. Hendrickson; Maryann Mazer-Amirshahi; Caitlin Bonney; Michele Burns; Diane P. Calello; Suzanne Doyon; Jeremy Hardin; Hannah Hays; Diane E. Hindman; Erica Liebelt; Michael J. Moss; Lewis Nelson; et al. (Journal of Medical Toxicology, 2026)

A mixed methods approach to better understand and steer multifunctional forestry in mountain regions of Europe - Maria Nijnik; Mariana Melnykovych; Simone Martino; Simo Sarkki; Albert Nijnik; Serhiy Kopiy; Leonid Kopiy; Katy Joyce; Chen Wang; Sam Poskitt; David Miller (Forest Policy and Economics, 2026)

Retraction notice to “Biochar for urban agriculture: Impacts on soil chemical characteristics and on Brassica rapa growth, nutrient content and metabolism over multiple growth cycles” [Sci. Total Environ. 727 (2020) 138742] - Shuang Song; Srishti Arora; Anna Karen C. Laserna; Ye Shen; Brian W.Y. Thian; Jia Chin Cheong; Jonathan K.N. Tan; Zhongyu Chiam; Siew Lee Fong; Subhadip Ghosh; Yong Sik Ok; Sam F.Y. Li; et al. (Science of The Total Environment, 2026)

New insights of aptamer as tools for food allergen management: From novel detection strategies to active control - Shuo Qi; Xiaoze Dong; Eslam M. Hamed; Sam Fong Yau Li; Xiaodong Lu; Erzheng Su; Zhouping Wang (Chemical Engineering Journal, 2026)

Jurassic megaspore Minerisporites institus Marcinkiewicz, 1960 from the Sichuan Basin, South China - Junhui Li; Linbo Ju; Qiang Li; Youzhi Wang; Zhiguo Wang; Sam M. Slater; Jungang Peng (Review of Palaeobotany and Palynology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

High hydrostatic pressure mitigates light-induced degradation of volatiles and phenolic compounds in seabuckthorn pear blends - Jianfeng Wang; Yonghao Chen; Rong Zhang; Shengbin Ma; Faisal Eudes Sam; Jixin Li; Yang Bi; Yumei Jiang (Food Chemistry, 2026)

Adaptive pattern learning particle swarm optimization for large-scale optimization - Zhi-Tao Lai; Zi-Jia Wang; Shuai Liu; Zong-Gan Chen; Zhi-Hui Zhan; Sam Kwong; Jun Zhang (Swarm and Evolutionary Computation, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Haploid embryogenic cultures of maize (Zea mays L.): stability, doubling efficiency, and use in gene editing - Charles Armstrong; Andrei Kouranov; Michelle Gasper; Sam Yang; Daniel Karcher; Huai Wang; Nicholas Homa; Steven Beach; Yuanji Zhang; Larry Gilbertson (In Vitro Cellular & Developmental Biology - Plant, 2026)
Embryogenic cultures were initiated from haploid and diploid seedlings of maize inbred LH244 and monitored for ploidy stability by flow cytometry over the course of six mo. Both culture types were transformed with three different constructs using Agrobacterium tumefaciens to compare transformation and gene editing frequencies. Paromomycin resistant cell lines were split prior to plant regeneration, and half of the tissue was treated with colchicine to induce chromosome doubling (a “mock” treatment without colchicine was used for the diploid target tissues). Ploidy measurements were taken on transgenic cell lines immediately prior to the doubling treatment and again approximately six wk later prior to plant regeneration. T0 plants were sampled and assessed for ploidy, transgene copy number, and Cas12a (LbCpf1) mediated gene editing. Chromosome stability of haploid cultures was excellent within three mo of initiation, and cultures remained predominantly haploid even after six mo in culture. Transformation frequencies of haploid and diploid cultures were comparable. A simple colchicine treatment of haploid callus was reasonably effective for doubling chromosome number to produce dihaploid plants. Chlorophyll deficient T0 plants were observed only from the haploid cultures, an indication of the immediate phenotypic display of recessive mutations. Editing frequency at the ch3_reg1_1.1 gRNA target site was very high for both haploid and diploid cultures. As expected, diploid plants derived from the haploid cultures were primarily homoallelic, and those from diploid cultures primarily biallelic. The results provided a framework for future editing work or mutational studies in maize using haploid embryogenic callus as the starting material.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Advances in thermoelectric coupling catalysis for CO2 reduction: Synergistic mechanisms, catalyst development, and application perspectives - Mengke Niu; Lei Wang; Linjie Cai; Jia Liu; Xuan Lin; Jun Yu; Sam Toan; Zhaoteng Xue; Dongsen Mao (Journal of Environmental Chemical Engineering, 2025)

Fusing bacteriophage specificity with MOF nanozyme catalysis to construct an AI-enhanced platform for simultaneous pathogen detection and eradication - Zixin Ming; Menghan Zhou; Xi Liu; Peng Guan; Sam R. Nugen; Harish Menghwar; Chenxi Huang; Xiaohong Wang (Chemical Engineering Journal, 2025)

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

Superhydrophilic MoS2@Polypyrrole hydrogel with dual photothermal-water activation properties for synergistic solar steam generation - Shengyi Wang; Cunxiu Zhang; Zhimeng Tang; Yiming Zhang; Sam Zhang; Deen Sun; Mingming Guo (Desalination, 2025)

Air-template assisted enhancement of solar steam generation - Shengyi Wang; Cunxiu Zhang; Zhimeng Tang; Deen Sun; Sam Zhang; Mingming Guo (Chemical Engineering Journal, 2025)

Maximum nutrition, minimum waste – exploring attitudes and behaviours towards food waste and ‘root-to-tip’ dining within the home - Georgia Browne; Fiona Lavelle; Gillian Brooks; Fatima Wang; Balazs Bajka; Peter Ellis; Graeme Collie; Eric Wu; Sam Jackson; Rachel Gibson (Appetite, 2025)

Fluorine-free membranes with microspheres and dual-scale fiber networks for highly effective waterproofness and breathability - Jiwang Chen; Jiajia Wu; Fei Wang; Sam S. Yoon; Bin Ding (Chemical Engineering Journal, 2025)

Bi-stage learning differential evolution for multimodal optimization problems - Chang-Long Wang; Zi-Jia Wang; Yi-Biao Huang; Dan-Ting Duan; Zhi-Hui Zhan; Sam Kwong; Jun Zhang (Swarm and Evolutionary Computation, 2025)

Investigating indoor VOC complexities in rural Beijing: Environmental, resident behavioral, and household energy-use paradigms - Jian Ma; Xiaojing Zhu; Xiaoying Li; Xiang Zhang; Fangxin Zhao; Anqi Zhao; Kaibing Xue; Qinping Song; Lijing Wang; Xin Zhang; Ellison Carter; Sam Harper; et al. (Building and Environment, 2025)

Establishment of a high-throughput scale-down clone screening platform for intensified fed-batch culture of CHO cells - Haiyan Luo; Shuai Wang; Collin Chong; Lile Wang; Xiaojun Sun; Qian Guo; Sam Zhang; Xiaoyue Chen; Hang Zhou; Weichang Zhou (Biotechnology Letters, 2025)

Joule heating of CuO-ZnO/Ni foam catalyst for high H2 production and energy-saving of methanol decomposition: From the performance to mechanism - Xuechen Zhou; Limo He; Chiyu Wang; Yufan Yang; Yanglin Chen; Song Hu; Sam Fong Yau Li; Yifei Sun; Sheng Su; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2025)

Effect of by-products-based diet and intramuscular fat content on volatile compounds from pork - Lisha Wang; Eline Kowalski; Sam Millet; Marijke Aluwé; Els Vossen; Stefaan De Smet (Meat Science, 2025)

Sex-specific trade-off under marine heat wave and food limitation: Insights from bioenergetic and intestinal microbiome in mussels - Yueyong Shang; Xueqing Chang; Fahim Ullah Khan; Sam Dupont; Menghong Hu; Youji Wang (Aquaculture, 2025)

Energy-saving research on the separation of isopropyl acetate and isopropanol azeotrope using pressure-swing distillation based on phase equilibrium - Lianzheng Zhang; Zhihong Shen; Jian Zhong; Zeyu Hu; Yixin Ma; Shanshan Liu; Jun Gao; Sam Fong Yau Li; Yinglong Wang (Process Safety and Environmental Protection, 2025)

Microwave-treated layered graphite for highly efficient solar-powered seawater desalination and wastewater treatment - Shengyi Wang; Cunxiu Zhang; Zhimeng Tang; Fangqiang Yuan; Kun Huang; Yichuan Zhang; Deen Sun; Mingming Guo; Sam Zhang (Desalination, 2025)

The potential water quality impacts of hard-rock lithium mining: Insights from a legacy pegmatite mine in North Carolina, USA - Gordon D.Z. Williams; Sam Saltman; Zhen Wang; D. Morgan Warren; Robert C. Hill; Avner Vengosh (Science of The Total Environment, 2024)

Impacts of ash-induced environmental alkalinization on fish physiology, and their implications to wildfire-scarred watersheds - Garfield T. Kwan; Trystan Sanders; Sammuel Huang; Kristen Kilaghbian; Cameron Sam; Junhan Wang; Kelly Weihrauch; Rod W. Wilson; Nann A. Fangue (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Transcriptome and metabolite profiles reveal the role of benzothiadiazole in controlling isoprenoid synthesis and berry ripening in chardonnay grapes - Yumei Jiang; Jianfeng Wang; Yuqi Han; Bo Wang; Chunni Lei; Faisal Eudes Sam; Jixin Li; Tengzhen Ma; Bo Zhang; Lidan Feng (Pesticide Biochemistry and Physiology, 2024)

Deoxygenated pyrolysis-gasification of biomass for intensified bio-oil and syngas co-production with tar abatement - Tingwei Wang; Hanpeng Liu; Sam Toan; Zhao Sun; Zhiqiang Sun (Fuel, 2024)

Moving to a new normal: Analysis of shifting climate normals in New Zealand - Raghav Srinivasan; Trevor Carey‐Smith; Linda Wang; Andrew Harper; Sam Dean; Gregor Macara; Ruotong Wang; Stephen Stuart (International Journal of Climatology, 2024)
New Zealand's National Institute of Water and Atmospheric Research publishes climate normals for New Zealand that are used for reporting the regional state of the climate, climate extremes and variability. Temperature and precipitation patterns are affected by both anthropogenic climate change and natural climate variability which in turn affect the climatological normal values calculated every decade. This study investigates how New Zealand's normals for temperature and precipitation have shifted over time at the national, regional and seasonal scales from the 1941–1970 period to the 1991–2020 period. Contrary to WMO recommendations, but aligned with many other countries, New Zealand's climate normals have traditionally not undergone homogenisation. The impact of introducing some homogenisation in the latest 1991–2020 normals, in contrast to historical non‐homogenized station normals, has been assessed using a new homogenized “Seventeen‐Station” temperature series from 1941 to 2020. We demonstrate that interpolating sparse non‐homogenized normals spatially to a grid can produce significant erroneous patterns and therefore undermine the accuracy of the conclusions drawn when using such normals. We find that the historical non‐homogenized temperature normals have a consistent negative bias in the long‐term trend at national, regional and seasonal scales. Our analysis of homogeneity tested precipitation showed consistent decreases at a national scale across all normal periods relative to the 1951–1980 precipitation normal. We also highlight how fixed period temperature and precipitation normals do not fully reflect the current state of a climate that is influenced by decadal variability and global warming. To derive normals fit for use in a changing climate it is suggested that automated methods for broad data homogenisation be developed along with alternative methods to derive normals that account for a non‐stationary climate.

Effect of agglomeration on nickel extraction and sulfur release from ultramafic nickel sulfide concentrates - Fanmao Wang; Sam Marcuson; Reda Elsawi; Lucy Liu; Jahir Mion Ramos; Mike Walker; Mansoor Barati (Minerals Engineering, 2024)

Size-dependent effects of plastic particles on antioxidant and immune responses of the thick-shelled mussel Mytilus coruscus - Shixiu Wang; Yichi Ma; Fahim Ullah Khan; Sam Dupont; Wei Huang; Zhihan Tu; Yueyong Shang; Youji Wang; Menghong Hu (Science of The Total Environment, 2024)

Highly efficient catalytic direct air capture of CO2 using amphoyeric amino acid sorbent with acid‐base bi‐functional 3D graphene catalyst - Lei Wang; Yanyang Gao; Jianmin Luo; Xiaoxing Wang; Richard Davis; Jianjia Yu; Dongsen Mao; Fangqin Cheng; Yun Hang Hu; Sam Toan; Maohong Fan (Chemical Engineering Journal, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Toxic effects of triphenyltin on the development of zebrafish (Danio rerio) embryos - Ying Qiao; Yongbing Zhou; Xuemin Zhang; Sam Faulkner; Hui Liu; Li Wang (Science of The Total Environment, 2023)

Prescribed performance control for dynamic positioning vessels with a dynamic event-triggered mechanism - Haibin Wang; Wenbo Xie; Peng Wang; Yuanhui Wang; Shuzhi Sam Ge (Ocean Engineering, 2023)

Combined effect of salinity and hypoxia on digestive enzymes and intestinal microbiota in the oyster Crassostrea hongkongensis - Zhe Xie; Yuting Li; Kai Xiong; Zhihan Tu; Khor Waiho; Chuangye Yang; Yuewen Deng; Saishuai Li; James K.H. Fang; Menghong Hu; Sam Dupont; Youji Wang (Environmental Pollution, 2023)

Boosting hydrogen production via deoxygenation-sorption-enhanced biomass gasification - Zhao Sun; Tingwei Wang; Rongjun Zhang; Hongwei Li; Yu Wu; Sam Toan; Zhiqiang Sun (Bioresource Technology, 2023)

Impact of sea ice transport on Beaufort Gyre liquid freshwater content - Sam B. Cornish; Morven Muilwijk; Jeffery R. Scott; Juliana M. Marson; Paul G. Myers; Wenhao Zhang; Qiang Wang; Yavor Kostov; Helen L. Johnson; John Marshall (Climate Dynamics, 2023)
The Arctic Ocean’s Beaufort Gyre (BG) is a wind-driven reservoir of relatively fresh seawater, situated beneath time-mean anticyclonic atmospheric circulation, and is covered by mobile pack ice for most of the year. Liquid freshwater accumulation in and expulsion from this gyre is of critical interest due to its potential to affect the Atlantic meridional overturning circulation and due to the importance of freshwater in modulating vertical fluxes of heat, nutrients and carbon in the ocean, and exchanges of heat and moisture with the atmosphere. Here, we investigate the hypothesis that wind-driven sea ice transport into/from the BG region influences the freshwater content of the gyre and its variability. To test this hypothesis, we use the results of a coordinated climate response function experiment with four ice-ocean models, in combination with targeted experiments using a regional setup of the MITgcm, in which we rotate the surface wind forcing vectors (thereby changing the ageostrophic component of these winds). Our results show that, via an effect on the net thermodynamic growth rate, anomalies in sea ice transport into the BG affect liquid freshwater adjustment. Specifically, increased ice import increases freshwater retention in the gyre, whereas ice export decreases freshwater in the gyre. Our results demonstrate that uncertainty in the ageostrophic component of surface winds, and in the dynamic sea ice response to these winds, has important implications for ice thermodynamics and freshwater. This sensitivity may explain some of the observed inter-model spread in simulations of Beaufort Gyre freshwater and its adjustment in response to wind forcing.

Simulation of compound flooding in Japan using a nationwide model - Wei Huang; Yinglong Joseph Zhang; Zhuo Liu; Hao-Cheng Yu; Yi Liu; Sam Lamont; Yu Zhang; Feyera Hirpa; Ting Li; Brett Baker; Wang Zhan; Shabaz Patel; et al. (Natural Hazards, 2023)

Physiological responses to salinity change and diel-cycling hypoxia in gills of Hong Kong oyster Crassostrea hongkongensis - Zhe Xie; Jianhang Shi; Yuntian Shi; Zhihan Tu; Menghong Hu; Chuangye Yang; Yuewen Deng; Sam Dupont; Zhixiong Xu; Youji Wang (Aquaculture, 2023)

Automatic detection of locomotor play in young pigs: A proof of concept - Mona L.V. Larsen; Meiqing Wang; Sam Willems; Dong Liu; Tomas Norton (Biosystems Engineering, 2023)

Mesoporous MgO enriched in Lewis base sites as effective catalysts for efficient CO2 capture - Lei Wang; Yi Yao; Trinh Tran; Patrick Lira; Steven Sternberg P.E.; Richard Davis; Zhao Sun; Qinghua Lai; Sam Toan; Jianmin Luo; Yudai Huang; Yun Hang Hu; et al. (Journal of Environmental Management, 2023)

Synergism effect of low voltage electrostatic field and antifreeze agents on enhancing the qualities of frozen beef steak: Perspectives on water migration and protein aggregation - Yong Xie; Kai Zhou; Bo Chen; Sam Al-Dalali; Cong Li; Ying Wang; Zhaoming Wang; Hui Zhou; Peijun Li; Baocai Xu (Innovative Food Science & Emerging Technologies, 2023)

Aroma improvement of dealcoholized Merlot red wine using edible flowers - Faisal Eudes Sam; Tengzhen Ma; Jing Wang; Yuhua Liang; Wenjun Sheng; Jixin Li; Yumei Jiang; Bo Zhang (Food Chemistry, 2023)

Dynamic analysis of microbial communities and flavor properties in Merlot wines produced from inoculation and spontaneous fermentation - Lihong Liang; Yuwen Ma; Zhanzhan Jiang; Faisal Eudes Sam; Shuai Peng; Min Li; Jing Wang (Food Research International, 2023)

A phage-based magnetic relaxation switching biosensor using bioorthogonal reaction signal amplification for Salmonella detection in foods - Chenxi Huang; Junpeng Zhao; Rongsheng Lu; Jia Wang; Sam R. Nugen; Yiping Chen; Xiaohong Wang (Food Chemistry, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Molecular mechanisms of coronary microvascular endothelial dysfunction in diabetes mellitus: focus on mitochondrial quality surveillance - Danan Sun; Jin Wang; Sam Toan; David Muid; Ruibing Li; Xing Chang; Hao Zhou (Angiogenesis, 2022)

Management and Associated Toxicokinetics of Massive Valproic Acid Ingestion with High Flow Continuous Venovenous Hemodiafiltration - Grant Comstock; Kevin Kilgallon; George Sam Wang; David Bourne; Eliza Blanchette; Erin Stenson (Journal of Medical Toxicology, 2022)

Heritable DNA-free genome editing of canola (Brassica napus L.) using PEG-mediated transfection of isolated protoplasts - Vladimir Sidorov; Dafu Wang; Ervin D. Nagy; Charles Armstrong; Steven Beach; Yuanji Zhang; Jeanna Groat; Sam Yang; Peizhen Yang; Larry Gilbertson (In Vitro Cellular & Developmental Biology - Plant, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Association between non-optimal temperature and hospitalizations for gout in Anqing, China: a time-series analysis - Yi-Sheng He; Gui-Hong Wang; Zheng-Dong Wu; Napoleon Bellua Sam; Yue Chen; Jin-Hui Tao; Xin-Yu Fang; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2022)

Effects of stimulant medication on divergent and convergent thinking tasks related to creativity in adults with attention-deficit hyperactivity disorder - Molly McBride; Carrina Appling; Bradley Ferguson; Alyssia Gonzalez; Andrea Schaeffer; Amanda Zand; David Wang; Alinna Sam; Eric Hart; Aneesh Tosh; Ivan Fontcha; Sophia Parmacek; et al. (Psychopharmacology, 2021)

Gonadal antioxidant responses to seawater acidification and hypoxia in the marine mussel Mytilus coruscus - Guangen Xu; Hui Kong; Xueqing Chang; Sam Dupont; Hui Chen; Yuewen Deng; Menghong Hu; Youji Wang (Environmental Science and Pollution Research, 2021)

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Impacts of ocean acidification under multiple stressors on typical organisms and ecological processes - Kunshan Gao; Guang Gao; Youji Wang; Sam Dupont (Marine Life Science & Technology, 2020)

New insights into the role of mitochondria in cardiac microvascular ischemia/reperfusion injury - Jin Wang; Sam Toan; Hao Zhou (Angiogenesis, 2020)

Advancing Observation of Ocean Biogeochemistry, Biology, and Ecosystems With Cost-Effective in situ Sensing Technologies - Zhaohui Aleck Wang; Hassan Moustahfid; Amy V. Mueller; Anna P. M. Michel; Matthew Mowlem; Brian T. Glazer; T. Aran Mooney; William Michaels; Jonathan S. McQuillan; Julie C. Robidart; James Churchill; Marc Sourisseau; et al. (Frontiers in Marine Science, 2019)

Using canonical correlation analysis to produce dynamically based and highly efficient statistical observation operators - Eric Jansen; Sam Pimentel; Wang-Hung Tse; Dimitra Denaxa; Gerasimos Korres; Isabelle Mirouze; Andrea Storto (Ocean Science, 2019)
Observation operators (OOs) are a central component of any data assimilation system. As they project the state variables of a numerical model into the space of the observations, they also provide an ideal opportunity to correct for effects that are not described or are insufficiently described by the model. In such cases a dynamical OO, an OO that interfaces to a secondary and more specialised model, often provides the best results. However, given the large number of observations to be assimilated in a typical atmospheric or oceanographic model, the computational resources needed for using a fully dynamical OO mean that this option is usually not feasible. This paper presents a method, based on canonical correlation analysis (CCA), that can be used to generate highly efficient statistical OOs that are based on a dynamical model. These OOs can provide an approximation to the dynamical model at a fraction of the computational cost. One possible application of such an OO is the modelling of the diurnal cycle of sea surface temperature (SST) in ocean general circulation models (OGCMs). Satellites that measure SST measure the temperature of the thin uppermost layer of the ocean. This layer is strongly affected by atmospheric conditions, and its temperature can differ significantly from the water below. This causes a discrepancy between the SST measurements and the upper layer of the OGCM, which typically has a thickness of around 1 m. The CCA OO method is used to parameterise the diurnal cycle of SST. The CCA OO is based on an input dataset from the General Ocean Turbulence Model (GOTM), a high-resolution water column model that has been specifically tuned for this purpose. The parameterisations of the CCA OO are found to be in good agreement with the results from the GOTM and improve upon existing parameterisations, showing the potential of this method for use in data assimilation systems.

Elevated MeCP2 in Mice Causes Neurodegeneration Involving Tau Dysregulation and Excitotoxicity: Implications for the Understanding and Treatment of MeCP2 Triplication Syndrome - Kristen R. Montgomery; A. S. C. Louis Sam Titus; Lulu Wang; Santosh R. D’Mello (Molecular Neurobiology, 2018)

Differential cellular responses by oncogenic levels of c-Myc expression in long-term confluent retinal pigment epithelial cells - Yiping Wang; Xiangdong Cheng; Muhammad Kaleem Samma; Sam K. P. Kung; Clement M. Lee; Sung Kay Chiu (Molecular and Cellular Biochemistry, 2018)

Pediatric Concerns Due to Expanded Cannabis Use: Unintended Consequences of Legalization - George Sam Wang (Journal of Medical Toxicology, 2017)

Midpoint attractors and species richness: Modelling the interaction between environmental drivers and geometric constraints - Robert K. Colwell; Nicholas J. Gotelli; Louise A. Ashton; Jan Beck; Gunnar Brehm; Tom M. Fayle; Konrad Fiedler; Matthew L. Forister; Michael Kessler; Roger L. Kitching; Petr Klimes; Jürgen Kluge; et al. (Ecology Letters, 2016)
We introduce a novel framework for conceptualising, quantifying and unifying discordant patterns of species richness along geographical gradients. While not itself explicitly mechanistic, this approach offers a path towards understanding mechanisms. In this study, we focused on the diverse patterns of species richness on mountainsides. We conjectured that elevational range midpoints of species may be drawn towards a single midpoint attractor – a unimodal gradient of environmental favourability. The midpoint attractor interacts with geometric constraints imposed by sea level and the mountaintop to produce taxon‐specific patterns of species richness. We developed a Bayesian simulation model to estimate the location and strength of the midpoint attractor from species occurrence data sampled along mountainsides. We also constructed midpoint predictor models to test whether environmental variables could directly account for the observed patterns of species range midpoints. We challenged these models with 16 elevational data sets, comprising 4500 species of insects, vertebrates and plants. The midpoint predictor models generally failed to predict the pattern of species midpoints. In contrast, the midpoint attractor model closely reproduced empirical spatial patterns of species richness and range midpoints. Gradients of environmental favourability, subject to geometric constraints, may parsimoniously account for elevational and other patterns of species richness.

Down‐regulation of tissue N:P ratios in terrestrial plants by elevated CO 2 - Qi Deng; Dafeng Hui; Yiqi Luo; James Elser; Ying-Ping Wang; Irakli Loladze; Quanfa Zhang; Sam Dennis (Ecology, 2015)
Increasing atmospheric CO 2 concentrations generally alter element stoichiometry in plants. However, a comprehensive evaluation of the elevated CO 2 impact on plant nitrogen : phosphorus (N:P) ratios and the underlying mechanism has not been conducted. We synthesized the results from 112 previously published studies using meta‐analysis to evaluate the effects of elevated CO 2 on the N:P ratio of terrestrial plants and to explore the underlying mechanism based on plant growth and soil P dynamics. Our results show that terrestrial plants grown under elevated CO 2 had lower N:P ratios in both above‐ and belowground biomass across different ecosystem types. The response ratio for plant N:P was negatively correlated with the response ratio for plant growth in croplands and grasslands, and showed a stronger relationship for P than for N. In addition, the CO 2 ‐induced down‐regulation of plant N:P was accompanied by 19.3% and 4.2% increases in soil phosphatase activity and labile P, respectively, and a 10.1% decrease in total soil P. Our results show that down‐regulation of plant N:P under elevated CO 2 corresponds with accelerated soil P cycling. These findings should be useful for better understanding of terrestrial plant stoichiometry in response to elevated CO 2 and of the underlying mechanisms affecting nutrient dynamics under climate change.

Identification of sparse neural functional connectivity using penalized likelihood estimation and basis functions - Dong Song; Haonan Wang; Catherine Y. Tu; Vasilis Z. Marmarelis; Robert E. Hampson; Sam A. Deadwyler; Theodore W. Berger (Journal of Computational Neuroscience, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Erratum to: On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

Effects of Commonly Used Excipients on the Expression of CYP3A4 in Colon and Liver Cells - Leslie Tompkins; Caitlin Lynch; Sam Haidar; James Polli; Hongbing Wang (Pharmaceutical Research, 2010)

On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

Immunotherapy of Human Neuroblastoma Using Umbilical Cord Blood-Derived Effector Cells - Avadhut D. Joshi; Erin M. Clark; Peng Wang; Corey M. Munger; Ganapati V. Hegde; Sam Sanderson; Harish P. G. Dave; Shantaram S. Joshi (Journal of Neuroimmune Pharmacology, 2007)

C-fos and c-jun expressions in nitric oxide synthase immunoreactive neurons in the lateral geniculate nucleus of experimental glaucomatous rats - Xu Wang; Samuel Sam-Wah Tay; Yee-Kong Ng (Experimental Brain Research, 2002)

An immunohistochemical study of neuronal and glial cell reactions in retinae of rats with experimental glaucoma - Xu Wang; Samuel Sam-Wah Tay; Yee-Kong Ng (Experimental Brain Research, 2000)